Chemically and thermally stable lanthanide-doped Y2O3 nanoparticles for remote temperature sensing in catalytic environments. (28th April 2019) - Geitenbeek, Robin G.; Salzmann, Bastiaan B.V.; Nieuwelink, Anne-Eva; Meijerink, Andries; Weckhuysen, Bert M.
Graphical abstract: Highlights: Luminescent probes are reported for remote temperature sensing in chemical reactors. Lanthanide-doped Y2 O3 nanoparticles are stable and versatile temperature probes. Wide temperature and spectral ranges are assessed by different types of lanthanides. The Y2 O3 nanoparticles on α-Al2 O3 remained stable upon heating to 900 K for 12 h. Abstract: Luminescent nanoparticles have great potential for remote temperature sensing. Mapping of high temperature profiles under harsh conditions that are common in chemical reactors requires new thermally and chemically stable (nano)probes. Here, we report temperature dependent luminescence of Yb 3+ /Er 3+ -, Dy 3+ - and Eu 3+ -doped Y2 O3 nanoparticles (NPs). We have deposited these lanthanide-doped Y2 O3 NPs on α-Al2 O3, a non-porous catalyst support material. The NPs are strongly adsorbed on the surface and no sintering was observed upon heating to 900 K for 12 h. The high chemical and thermal stability of Y2 O3 makes these nanoprobes ideal for sensing in catalytic environments. A systematic study of the three types of luminescent NPs reveals that the temperature dependent luminescence of Yb 3+ /Er 3+, Dy 3+ and Eu 3+ serves different temperature ranges: lower T regime (300–800 K, accuracy < 5 K) for Yb 3+ /Er 3+, intermediate T for Dy 3+ (400–900 + K, accuracy < 15 K) and high T for Eu 3+ (550–900 + K, accuracy < 12 K). The superior thermal and chemical stability of the Y2 O3 /α-Al2 O3 host in combination with different luminescent lanthanide dopants results in a robust system that can be tailored to monitor temperatures in different regimes with the highest possible sensitivity.